Profile of acid-base disturbances in an intensive care unit of Fortaleza, Ceará, Brazil. - Rodrigues, Renan Barbosa; Farias de Araújo, Maria Cristina; Nascimento, Payron Augusto; Rodrigues, Patricia Barbosa; Soares Pereira, Ricardo Victor; Patrocinio, Manoel Claudio Azevedo (Journal of Health & Biological Sciences, 2014)
Introduction: Acid – base disturbances are entities caused by the deregulation of the concentration of bicarbonate ions, the concentration of hydrogen ions and the partial pressure of carbon dioxide in the blood. These disturbances modify most cell fuctions when present, jeopardizing the proper functioning of organs. Methods: Cross-sectional analytical study based upon data collected from medical files of patients in ICU as seen from August 1 to December 31, 2013 at the Dr. José Frota Institute in Fortaleza, Ceará. The variables studied were: age, sex, cause of ICU admission, pH, HCO3-, pO2, pCO2 , glomerular filtration rate ( GFR ), serum potassium concentrarion, serum magnesium concentration, serum creatinine and hemoglobin levels. Results: The most frequent disorders were primary respiratory alkalosis with 33 ( 38,4 % ) cases, 30 ( 34,9 % ) of metabolic alkalosis, 13 ( 15.1% ) of metabolic acidosis, 7 ( 8,2% ) did not present acid-base disorders and respiratory acidosis 3 ( 3,5%). Patients admitted with TBI had respiratory alkalosis as the most common primary disorder, followed by metabolic alkalosis, 16 ( 47,0 % ) and 13 ( 38,2 % ), respectively. The main disturbances were mixed respiratory alkalosis with metabolic alkalosis and respiratory alkalosis with metabolic alkalosis found in 15.12% of patients in each of these combinations. Conclusion:The importance of a detailed evaluation of acid-base disturbances is necessary since these disorders lead to higher mortality rates, so it is necessary to establish the main types of disorders that are associated with a particular cause of hospitalization .